Freakier Friday [videorecording (DVD)] - Weiss, Jordan; Weiss, Jordan; Hollander, Elyse; Curtis, Jamie Lee, 1958-; Lohan, Lindsay, 1986-; Butters, Julia, 2009-; Hammons, Sophia; Jacinto, Manny; Ramakrishnan, Maitreyi, 2001-; Chao, Rosalind; Harmon, Mark, 1951-; Murray, Chad Michael, 1981-; et al. (Disney, 2025)
"Tess's daughter Anna now has a daughter of her own and soon, a stepdaughter. As they navigate the joys and challenges when two families merge, lightning just may strike twice."--